2021
DOI: 10.3390/rs13173531
|View full text |Cite
|
Sign up to set email alerts
|

Projecting Future Vegetation Change for Northeast China Using CMIP6 Model

Abstract: Northeast China lies in the transition zone from the humid monsoonal to the arid continental climate, with diverse ecosystems and agricultural land highly susceptible to climate change. This region has experienced significant greening in the past three decades, but future trends remain uncertain. In this study, we provide a quantitative assessment of how vegetation, indicated by the leaf area index (LAI), will change in this region in response to future climate change. Based on the output of eleven CMIP6 globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…These projected changes in the LAI in the present study agree with the estimates for 2021–2050 using geographically weighted regression based on a regional simulation driven by 5 CMIP5 projections (Gao et al., 2017; Shi et al., 2018). The results from multiple linear regression with 11 CMIP6 projections similarly reported that the northeast is likely to become warmer and wetter, and hence have an increase in regional LAI (Yuan et al., 2021). Likewise, throughout the twenty‐first century, vegetation in China has a greening trend according to another study with 12 CMIP5 models (Zhou et al., 2020).…”
Section: Discussionmentioning
confidence: 91%
“…These projected changes in the LAI in the present study agree with the estimates for 2021–2050 using geographically weighted regression based on a regional simulation driven by 5 CMIP5 projections (Gao et al., 2017; Shi et al., 2018). The results from multiple linear regression with 11 CMIP6 projections similarly reported that the northeast is likely to become warmer and wetter, and hence have an increase in regional LAI (Yuan et al., 2021). Likewise, throughout the twenty‐first century, vegetation in China has a greening trend according to another study with 12 CMIP5 models (Zhou et al., 2020).…”
Section: Discussionmentioning
confidence: 91%
“…Climate data can be integrated with vegetation data in a statistical model to predict future changes in vegetation dynamics. This approach has shown promise in predicting future leaf area index (LAI) trends [51, 52], NDVI trends [53], and short-term prediction of NDVI as an early warning system for disasters such as famine and epidemic diseases [54], and the risk of Rift Valley fever (RVF) [55, 56]. These methods help our understanding of ecological dynamics and facilitate informed decision-making for sustainable resource management.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al investigated the impact of climate change on vegetation LAI in a global study [7]. Yuan et al studied vegetation phenological changes in Northeast China based on LAI [8]. These studies highlight the importance of LAI in understanding vegetation dynamics and its response to climate change.…”
Section: Introductionmentioning
confidence: 99%